Pole length and ground reaction forces during maximal double poling in skiing - Nilsson, J.; Jakobsen, V.; Tveit, P.; Eikrehagen, O. (Sports Biomechanics, 2003)
The purpose of the investigation was to study the relationship between thrust phase duration, ground reaction force, velocity increase after pole thrust and pole angles versus pole length during double poling in roller skiing. Seven male regional elite cross-coutnry skiers volunteered as subjecs for the study. The subjects performed a maximal double pole thrust on roller skis with each ot the three different ple lengths: 'short', self-selected (normal) and 'long'. The short and long poles were 7.5 shorter and 7.5 cm longer than the self-selected pole length. The subjects made seven maximal pole thrusts with each pole length, which were randomly selected during 21 trials. For each trial the subjects accelerated from a 1.2 m high downhill slope attaining a speed of 3.92 m.s-1 before making a maximal double pole thrust on a force plate placed at the bottom of the slope. The vertical (Fz), anterior-posterior (Fy) and medio-lateral (Fx) reaction forces of the left pole were measured by the force plate. The positions of the pole were recorded in 3-D by an opto-electronic system. Thrust phase duration, impulse, mean force, velocity increase after pole thrust and pole angles were calculated from the recorded data. Double poling with long poles produced a significantly larger propulsive anterior-posterior reaction force impulse and velocity increase than normal (p<.05) and short poles (p<.05). This was in spite of a larger mean anterior-posterior reactoin forces being produced with short poles. Thus, thrust phase duration was a primary factor in determining propulsive anterior-posterior impulse. For the practitioner, the results can be useful in the selection of pole length when the aim is to increase thrust phase duration, anterior-posterior force impulse and velocity.